Discursive Mediation in Translation: Representation of the Harry Wu topic in the Chinese translations of Living History - Wang, Hui; Zhu, Chunshen (Meta, 2009)
AbstractThis paper describes how mediation in translation is realized by means of inclusion and exclusion of information at the selection stage and discursive deviations at the presentation stage in the process of target text production. It discusses the effect of mediation in relation to two types of the target text recipients, one is termed professional readers representing the censoring authorities and the other the intended reading public, and their respective socio-cultural backgrounds. Our argument in this paper is that an investigation of translation from the perspective of mediation helps reveal the power struggle underlying the translation process. The detailed description of the textual realization of mediation, in particular, helps create an awareness of the various ways the target text producer may take to mediate the translation process to achieve a compromise between the author’s interests and the professional readers’ political concerns so as to get the translation published.